Choice of practice-task order enhances golf skill learning. (September 2020) - An, Jongseong; Lewthwaite, Rebecca; Lee, Seungmin; Wulf, Gabriele
Abstract: Objective: The purpose of the present study was to examine whether supporting learners' autonomy, by giving them a small choice (i.e., order of practice devices) while practicing a golf putting task, would enhance learning, confidence, and positive affect. Design: Experimental, between-participants, and yoked design. Methods: Two groups of participants practiced a golf-putting task under choice or control conditions. Choice group participants selected the order of three practice devices (visual cues, auditory cues, chest bar), while control group participants had to use those devices in the same order as their yoked choice-group counterpart. Learning was assessed by a delayed retention test. In addition to putting accuracy, we measured learners' perceived choice, confidence, and positive affect. Results: Practice and retention performance were enhanced in the choice relative to the control group. Perceived choice, confidence, and positive affect were rated higher by choice group participants as well. Conclusions: Providing performers with a small choice during task practice had motivational benefits that resulted in enhanced learning, increased confidence, and more positive emotional responses. Highlights: We examined the effects of a small choice on the learning of a golf-putting task. In a choice group, participants selected the order of three devices during practice. Relative to a control condition, having a choice enhanced learning. Confidence and positive affect were higher in the choice group as well. Autonomy support has motivational benefits that facilitate motor skill learning.